The effect of different remineralizing agents on initial carious lesions - Mohammed Alhamed; Faisal Almalki; Ahmad Alsolami; Tariq Alotaibi; Wahdan Elkwatehy (Saudi Dental Journal)
Background: Dental caries is one of the most prevalent diseases worldwide. Remineralization is the treatment for an initial caries lesion to arrest the progression of the lesion to cavitated stages. The DIAGNOdent device excelled in sensitivity for detecting initial carious lesions compared to a visual examination. Objectives: This study aimed to evaluate and compare the effectiveness of three different remineralizing agents on initial carious lesions. Material and methods: The present clinical study was carried out on 90 initial carious lesions detected by a DIAGNOdent device. The study samples were classified into three groups (30 lesions in each group) according to remineralizing agents: group A (tri-calcium phosphate varnish), group B (fluoride varnish) and group C (nano-hydroxyapatite gel). The baseline scores of initial caries were recorded by DIAGNOdent. Then, all teeth were polished, isolated, and dried, and the remineralizing agents were applied for four minutes once weekly for four weeks. At the fifth week, the caries was recorded to evaluate which remineralizing agents had the best remineralizing effect. Results: There was no significant difference among baseline records on occlusal and proximal surfaces among the three groups. While in follow-up records there was a significant difference in fissure caries surface among the three groups (p-value 0.006), in smooth surface caries, there was no significant difference (p-value 0.058). However, there was a highly significant difference between baseline and follow-up records in each material on both surfaces. Conclusion: The present study confirmed the remineralizing effectiveness of the three agents. The most effective remineralizing agent was nano-hydroxyapatite.